2015
DOI: 10.1108/bfj-11-2013-0330
|View full text |Cite
|
Sign up to set email alerts
|

Application of health and taste attitude scales in Serbia

Abstract: Purpose – Consumers’ attitudes, especially their attitudes towards health and taste, are significant in understanding and predicting dietary behaviour. In this research, Health and Taste Attitude Scales (HTAS) developed by Roininen et al. in 1999 for measuring health and taste attitudes of consumers, were applied in Serbia. The purpose of this paper is to find out whether the same sub-scales can be identified as in HTAS applications abroad, to test the predictive validity of HTAS and to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
3
12
1
2
Order By: Relevance
“…On the other hand, eating out was not widely recognized as social event just as preparing food was not understood as a task for the whole family. The most important dimensions are consistent with previous research conducted in domestic conditions (Grubor et al 2015).…”
Section: New Market Segmentation Knowledge In the Function Of Bioeconsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, eating out was not widely recognized as social event just as preparing food was not understood as a task for the whole family. The most important dimensions are consistent with previous research conducted in domestic conditions (Grubor et al 2015).…”
Section: New Market Segmentation Knowledge In the Function Of Bioeconsupporting
confidence: 90%
“…Although both, conservative and adventurous food consumers rank health among their priorities, this does not necessarily translate into consumption or preference to organic food, which is often associated with health (Hughner et al 2007). As for the conservative food consumers this partly resembles to the results of previous research whereby consumers in Serbia predominantly manifested their general interest in health by consuming functional food, while frequency of consumption of organic food is correlated only with their interest in natural products (Grubor et al 2015).…”
Section: New Market Segmentation Knowledge In the Function Of Bioeconsupporting
confidence: 81%
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…In their works, Lusk et al [ 63 ] saw that INF increased the probability of selecting non-clone or non-hormone milk as opposed to the clone or hormone variety. Many research works undertaken in different countries have revealed that INF significantly affects eating healthy [ 64 , 65 , 66 , 67 , 68 ], organic [ 69 ] and traditional foods [ 46 , 70 ], and eating unhealthy [ 66 , 67 ] and convenience foods [ 71 ]. Roininen and Tuorila [ 72 ] and Zandstra et al [ 73 ] found that INF did not affect unhealthy or healthy eating.…”
Section: Consumer Perceptions Of and Attitudes To Natural Food Promentioning
confidence: 99%